Lactate Measurements in Sepsis-Induced Tissue Hypoperfusion: Results From the Surviving Sepsis Campaign Database*. Issue 3 (March 2015) - Casserly, Brian; Phillips, Gary S.; Schorr, Christa; Dellinger, R. Phillip; Townsend, Sean R.; Osborn, Tiffany M.; Reinhart, Konrad; Selvakumar, Narendran; Levy, Mitchell M.
Abstract : Objective: The Surviving Sepsis Campaign guidelines recommend obtaining a serum lactate measurement within 6 hours of presentation for all patients with suspected severe sepsis or septic shock. A lactate greater than 4 mmol/L qualifies for administration of early quantitative resuscitation therapy. We evaluated lactate elevation (with special attention to values > 4 mmol/L) and presence or absence of hypotension as a marker of clinical outcome. Design and Setting: The Surviving Sepsis Campaign developed a database to assess the overall effect of the sepsis bundles as a performance improvement tool for clinical practice and patient outcome. This analysis focuses on one element of the Surviving Sepsis Campaign's resuscitation bundle, measuring serum lactate in adult severe sepsis or septic shock patients and its interaction with hypotension. This analysis was conducted on data submitted from January 2005 through March 2010. Subjects: Data from 28, 150 subjects at 218 sites were analyzed. Interventions: None. Measurements and Main Results: Unadjusted analysis of the 28, 150 observations from the Surviving Sepsis Campaign database demonstrated a significant mortality increase with the presence of hypotension in conjunction with serum lactate elevation greater than 2 mmol/L. On multivariable analysis, only lactate values greater than 4 mmol/L, in conjunction with hypotension, significantly increased mortality when compared with the referent group of lactate values less than 2 mmol/L and not hypotensive. Mortality was 44.5% in patients with combined lactate greater than 4 mmol/L and hypotension when compared with 29% mortality in patients not meeting either criteria. Conclusions: Serum lactate was commonly measured within 6 hours of presentation in the management of severe sepsis or septic shock in this subset analysis of the Surviving Sepsis Campaign database in accordance with the Surviving Sepsis Campaign guidelines. Our results demonstrate that elevated lactate levels are highly associated with in-hospital mortality. However, only patients who presented with lactate values greater than 4 mmol/L, with and without hypotension, are significantly associated with in-hospital mortality and is associated with a significantly higher risk than intermediate levels (2–3 and 3–4 mmol/L). This supports the use of the cutoff of greater than 4 mmol/L as a qualifier for future clinical trials in severe sepsis or septic shock in patient populations who use quantitative resuscitation and the Surviving Sepsis Campaign bundles as standard of care. Abstract : Supplemental Digital Content is available in the text.